The Sensory Profile of 5 Types of Sumatran Forest Honey - Winanti, Diki Danar Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Sumatra has a very large forest area so it has great potential to become a place for honey bee cultivation. The various honey produced has different characteristics depending on the source of the nectar. Research on sensory testing of Sumatran forest honey appears limited, with studies focusing more broadly on honey quality and properties. It is necessary to collect data on the sensory profile of Sumatran forest honey as a database that will help control the quality and ensure the authenticity of the honey. The purpose of this study is to determine the sensory profile of five types of Sumatran forest honey traded around Lampung Province. The method used a scoring test on color, aroma, taste, and viscosity. 30 trained panelists were used who had been selected and trained before conducting sample assessment. Data processing using ANOVA and further test Duncan Multiple Range Test (DMRT) with SPSS 27.0 software. The results showed that the five types of Sumatran forest honey tested had the same viscosity but had different color, aroma, and taste profiles. These distinctive and unique characteristics can enrich the biodiversity in Indonesia so it needs to be optimized for its benefits and preserved.